2002
DOI: 10.1291/hypres.25.731
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Sodium and Potassium in a Screened Cohort in Okinawa, Japan.

Abstract: Information regarding daily intake of sodium (Na) is useful for both normotensive and hypertensive subjects. We measured urinary excretion of sodium (U-Na) and urinary excretion of potassium (U-K) to estimate daily salt intake in a cohort of health screening subjects in Okinawa, Japan. Urine samples were obtained from 2,411 subjects (1,554 men and 857 women) who were examined on a half-day dry-doc at the Okinawa General Health Maintenance Association (OGHMA). Four hundred and one subjects were examined twice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
23
1
Order By: Relevance
“…The present data showed that the average intake of protein is not high in Okinawa. We also reported that the salt intake was smaller than that of the Japanese national average (14). Therefore, we speculate that the high incidence of ESRD in Okinawa is not directly related to dietary habits.…”
Section: Discussionmentioning
confidence: 68%
“…The present data showed that the average intake of protein is not high in Okinawa. We also reported that the salt intake was smaller than that of the Japanese national average (14). Therefore, we speculate that the high incidence of ESRD in Okinawa is not directly related to dietary habits.…”
Section: Discussionmentioning
confidence: 68%
“…The logarithm of urinary albumin excretion in the third quartile was significantly lower than in the first (Po0.01) or second (Po0.05) quartile of daily salt intake. *Cut points for the quartiles of daily salt intake were 8, 10 and 12 g. Low daily salt intake and albuminuria K Sakabe et al values obtained from the spot urine method correlated highly with those obtained from 24-h urinary sodium excretion, 19 and the usefulness of the spot urine method has been confirmed in population studies 20 and in hypertensive patients. 21 We speculate that excessive dietary salt restriction leads to increased angiotensin II and aldosterone levels, chiefly via an increase in plasma renin activity.…”
Section: Discussionmentioning
confidence: 73%
“…Daily sodium excretion values obtained by the SMU method show a strong correlation with those estimated by the 24-h collection (R¼0.73). The usefulness of the SMU method has been confirmed in population studies 5,11,12 and in hypertensive patients. 13 Although the posture that should be adopted for the SMU method was not specified by the original authors, 10 posture is known to affect the urinary sodium:creatinine ratio 14,15 and could possibly influence the estimation of daily salt intake by this method.…”
Section: Introductionmentioning
confidence: 84%